2017
DOI: 10.32598/sija.13.10.240
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Report Home Environment Screening Tool for Screening Fall Risk in Iranian Elder Homes

Abstract: Objectives Older people are at risk of falling and its complications more than other age groups. Evaluation of environmental hazards requires time and money. So it seems necessary to design a self-report questionnaire for initial screening. This study aims to develop a self-report tool for falling risk assessment in Iranian older people. Methods & Materials After approval of the Ethics Committee of Iran University of Medical Sciences, an expert group prepared and wrote the study items using simple words and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Although the internal validation using the bootstrap optimism-corrected C-statistics showed that the possibility of overfitting and optimism was low, external validation in the independent study population is needed [ 52 ]. In terms of the Modified HOME FAST-SR, the finding that its predictive validity was similar to three forms of the Thai-HFHAT assessments also implied that this instrument was well applicable to the international context, as indicated by the fact that a number of investigators had applied this instrument to their home countries [ 14 – 16 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the internal validation using the bootstrap optimism-corrected C-statistics showed that the possibility of overfitting and optimism was low, external validation in the independent study population is needed [ 52 ]. In terms of the Modified HOME FAST-SR, the finding that its predictive validity was similar to three forms of the Thai-HFHAT assessments also implied that this instrument was well applicable to the international context, as indicated by the fact that a number of investigators had applied this instrument to their home countries [ 14 – 16 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%